2020
DOI: 10.1111/hir.12323
|View full text |Cite
|
Sign up to set email alerts
|

Personal, technical and organisational factors affect whether physicians seek answers to clinical questions during patient care: a literature review

Abstract: Background Numerous questions are generated for physicians during patient care. Facilitators and barriers affect the physicians' clinical information‐seeking behaviour. While most health studies have focused on barriers, few have dealt with facilitators. Objective This review aimed to identify facilitators in physicians' information‐seeking behaviour to help respond to clinical questions raised during patient care. Methods A narrative review was conducted, and 9 databases were searched. Selection criteria incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…The review article by Daei et al (2021) considers what factors make it easy for clinicians to seek answers to clinical questions when seeing patients. Instead of focussing on barriers, their literature review identifies three types of facilitators: personal, technical and organisational.…”
Section: In This Issue…mentioning
confidence: 99%
“…The review article by Daei et al (2021) considers what factors make it easy for clinicians to seek answers to clinical questions when seeing patients. Instead of focussing on barriers, their literature review identifies three types of facilitators: personal, technical and organisational.…”
Section: In This Issue…mentioning
confidence: 99%
“…Daei et al (2021) start the issue by looking at the facilitators in physicians’ information‐seeking behaviour. Clinical questions raised during patient care requires systems that encourage doctors to seek answers during consultations and this review explores personal, technical and organisational facilitators to this process.…”
Section: In This Issue…mentioning
confidence: 99%
“…Primary care doctors need to access information during the consultation due to time constraints and the fact that most care is provided with the patient, doctor and information source in the same space. Previous studies have found that use of online clinical evidence resources improves the accuracy of answers to clinical questions, doctors’ confidence in decision-making and possibly outcomes 4–10…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that use of online clinical evidence resources improves the accuracy of answers to clinical questions, doctors' confidence in decision-making and possibly outcomes. [4][5][6][7][8][9][10] Despite the benefits of answering clinical questions at the point-of-care, concerns remain about this practice. Anecdotally, patients have reported dissatisfaction with their doctor using online search engines to assist in medical decision-making.…”
Section: Introductionmentioning
confidence: 99%